Hepatitis C Virus in Children: Trying to Overcome the Domestic and Global Challenges of Cases and Cost. (16th October 2019) - Perfect, Chase; Jhaveri, Ravi
Abstract: Over the last decade, Hepatitis C virus has persisted and evolved as a domestic and global health challenge for adults and children. The challenges involve both increased cases in the United States and cost of treatment both in the US and globally.